Proposição de um modelo de avaliação do serviço de fornecimento de refeições em restaurantes universitários - Rodrigues, Tobias Abich (2021)
This study aimed to answer the following research problem: How to assess the quality of outsourced meal supply services at the Federal University of Santa Maria? To answer the question, it was proposed to apply an adapted version of the SERVPERF and Corrêa and Gianesi scales for evaluating services in university restaurants at UFSM. The data collection process consisted of two stages: the first, with a qualitative approach, through the application of interviews; and the second, with a quantitative approach, through the application of a survey. The applied interviews were of the semi-structured type and were intended to carry out the mapping of management processes for meal supply contracts. The survey was developed through the application of questionnaires in a sample of 720 users of University Restaurants. The instrument was divided into two blocks, the first containing questions about the profile of the participants and aimed to measure the perception of quality through the evaluation of the performance of the service providing meals in University Restaurants. Qualitative results were analyzed through content analysis techniques and quantitative results through statistical analysis. The triangulation of methods revealed that UFSM managers are interested in the development of a methodology for the assessment of catering services in the RUs by the user public through satisfaction surveys linked to the Results Measurement Index (IMR). The need to appoint and train contract inspectors to avoid the accumulation of functions and improve the performance of contract management was also highlighted. Regarding the provider, the proper management of human resources was related to the users' dissatisfaction with the waiting time in line and the credit sale time. Overall, the evaluation of more than 80% of users indicated that the performance of the service provided in the RUs is good. Factor analysis showed that the factors Employees, Food, Facilities, Cleaning, Breakfast, Benefit Cost and Dessert account for 61.514% of the explained variance. It was concluded that the implementation of user satisfaction surveys linked to the IMR can bring benefits to the management of meal supply contracts at UFSM. For this reason, action plans were drawn up to institute satisfaction surveys in order to optimize control over the performance of services. The plans developed to effect the composition and training of contract management teams to apply satisfaction surveys and use the IMR meet this objective. In addition, to increase the level of user satisfaction, plans were drawn up for the implementation of improvements to the facilities and the proper management of the queue in the RUs.